Dual-function hydrotalcite-derived adsorbents with sulfur storage properties: Dyes and hydrotalcite fate in adsorption-regeneration cycles - Stawiński, Wojciech (2017)
Thermal treatment of hydrotalcite at increasing temperatures resulted in formation of mixed oxides that exhibited different adsorption behavior toward anionic and cationic industrial dyes. The material annealed at 450 °C was characterized by the highest maximum adsorption capacity for both types of dyes. The adsorption was strongly pH dependent and for the anionic dye abatement low pH was favored whilst higher pH was more preferable for removal of the cationic dye. According to the equilibrium experiments, the maximum adsorption capacity increased from 179 ± 5 to 291 ± 8 mg g−1 in case of the anionic dye at pH 3.5 and from 6 ± 2 to 48 ± 2 mg g−1 in case of the cationic dye at pH 8.0, on starting and thermally treated material at 450 °C, respectively. Detailed characteristics of spent adsorbent and its reconstructed form revealed that after each cycle of adsorption and thermal regeneration the maximum adsorption capacity of the material decreased due to changes in the structure and accumulation of sulfur compounds. Evolution of specific surface area and porosity was correlated with annealing temperatures and behavior of dye's residues.